Determination the antioxidante activity of seeds, leaves and shelled panicles of different varieties of pearl millet (Pennisetum glaucum (L). Br) cultivated from Bordj Bou Arreridj region - Ghaoui, Samia; Hadbaoui, Zineb; Belhadi, Badereddine (Université Amar Telidji - Laghouat - Département des sciences de la matière, 2023)
Pearl millet is a nutritional plant with many benefits, it’s considered to be a source of various antioxidants (total phenols, tannins..etc) , that works to inhibit the free radicals effect in the human body , this work was devoted to extract the phenolic compounds from different parts of local pearl millet of bordj bou arrereidj ,this parts was divided to (seeds, panicle shelled and leafs ) , the antioxidant activity was evaluated by two chemical tests FRAP and DPPH . The results showed that these local varieties are promising source of phenolic compounds, the best yield was found in the leaves of M11 extracted by methanol with (9.26%). The total phenolic content extracted by acetone ranged from (0.11to1.53 mgGAE/g) and by methanol ranged from (0.69to 2.48 mgGAE/g) the results by (acetone / H2O:70/30)and (methanol:80/20) was (0.62 to 2.72 mgGAE/g) and (0.12 to 2.52 mgGAE/g) respectevly , while for tannins content higher results was recorded by acetone and methanol extracts where they mark ( 10.39 mgEC/g) (11.61mgEC/g) respectively and for (acetone / H2O:70/30) and (methanol:80/20) the results was (10.66 mgEC/g) (4.77 mgEC/g) . The results of antioxidant activity was high in both DPPH and FRAP , the best scavenging result was given by the leaves of M3with (11,61VEAC) and (2.34 AEAC) by panicle shelled of M3 for FRAP reducing result. the variance analysis (ANOVA) results of the solvent systems and varieties showed a significant variance which means high difference in the parameters studied while the plant parts showed two significant difference in (TPC) and DPPH. The correlation study proves that (TPC) contribute in the antioxidant activity, where, tannins content is related to the FRAP and it’s not related to DPPH scavenging activity.